Bronchial thermoplasty: Long-term safety and effectiveness in patients with severe persistent asthma - Wechsler, Michael E.; Laviolette, Michel; Rubin, Adalberto S.; Fiterman, Jussara; Lapa e Silva, Jose R.; Shah, Pallav L.; Fiss, Elie; Olivenstein, Ronald; Thomson, Neil C.; Niven, Robert M.; Pavord, Ian D.; Simoff, Michael; et al. (Journal of allergy and clinical immunology, 2013)
Bronchial thermoplasty (BT) has previously been shown to improve asthma control out to 2 years in patients with severe persistent asthma. We sought to assess the effectiveness and safety of BT in asthmatic patients 5 years after therapy. BT-treated subjects from the Asthma Intervention Research 2 trial (ClinicalTrials.govNCT01350414) were evaluated annually for 5 years to assess the long-term safety of BT and the durability of its treatment effect. Outcomes assessed after BT included severe exacerbations, adverse events, health care use, spirometric data, and high-resolution computed tomographic scans. One hundred sixty-two (85.3%) of 190 BT-treated subjects from the Asthma Intervention Research 2 trial completed 5 years of follow-up. The proportion of subjects experiencing severe exacerbations and emergency department (ED) visits and the rates of events in each of years 1 to 5 remained low and were less than those observed in the 12 months before BT treatment (average 5-year reduction in proportions: 44% for exacerbations and 78% for ED visits). Respiratory adverse events and respiratory-related hospitalizations remained unchanged in years 2 through 5 compared with the first year after BT. Prebronchodilator FEV1 values remained stable between years 1 and 5 after BT, despite a 18% reduction in average daily inhaled corticosteroid dose. High-resolution computed tomographic scans from baseline to 5 years after BT showed no structural abnormalities that could be attributed to BT. These data demonstrate the 5-year durability of the benefits of BT with regard to both asthma control (based on maintained reduction in severe exacerbations and ED visits for respiratory symptoms) and safety. BT has become an important addition to our treatment armamentarium and should be considered for patients with severe persistent asthma who remain symptomatic despite taking inhaled corticosteroids and long-acting β2-agonists.